Structured Floral Arrangement Program Benefits in Patients With Neurocognitive Disorder - Mochizuki-Kawai, Hiroko; Kotani, Izumi; Mochizuki, Satoshi; Yamakawa, Yuriko (Frontiers in Psychology, 2018)
We attempted to clarify positive benefits in cognitive abilities and motivation during our cognitive intervention (Structured Floral Arrangement program: SFA program) for patients with neurocognitive disorder due to stroke, traumatic brain injury (TBI), and other related disorders. In this SFA program, participants are required to arrange cut flowers and leaves on absorbent foam according to an instruction sheet. In a previous study of patients with schizophrenia, our SFA program encouraged participants and contributed to stimulating their visuospatial process and memory. Here, 27 patients with neurocognitive disorders participated in this study. Sixteen patients were assigned to an SFA treated group and participated in six sessions during two phases plus to daily activities. Eleven non-treated patients engaged only daily activities during the same period. We compared apathy scale scores and neuropsychological scores between the SFA treated and non-treated patients. Their mean attendance rate was more than 90% during the two phases. SFA treated patients copied a Rey-Osterrieth complex figure more accurately than non-treated patients (P < 0.05) during the later intervention phase, whereas during the earlier phase, accuracy was comparable between treated and non-treated groups. In the SFA treated group, recall scores also improved (P < 0.01), and the positive outcomes were maintained for about 3 months (P < 0.05). The apathy scale scores did not show significant change in either the SFA treated or non-treated groups. Our present results suggest that the SFA program encouraged continuous participation to cognitive intervention and was useful for ameliorating dysfunctions in visuospatial memory and recognition in patients with neurocognitive disorder.